Descriptions of four new species of the Ambrysus signoreti Stål species complex (Heteroptera: Nepomorpha: Naucoridae - Reynoso-Velasco, Daniel; Sites, Robert W. (Zootaxa, 2019)
The genus Ambrysus Stål is the most species rich genus of Naucoridae. Multiple species groups in the genus have been proposed, including the North American Ambrysus signoreti Stål complex. Four new species belonging to the A. signoreti complex are described and illustrated: three from Mexico (Ambrysus brailovskyi Reynoso & Sites n. sp., A. henryi Reynoso & Sites n. sp., A. schuhi Reynoso & Sites n. sp.) and one from Mexico and Guatemala (A. sitesi Reynoso n. sp.), bringing the total number of described species of Ambrysus to 97.